Comparison between Transurethral Resection of Benign Prostatic Hyperplasia and Open Prostatectomy - يوسف محمد; كنعان محمد; ابراهيم همام (Latakia University Journal -Medical Sciences Series, 2020)
Background: The purpose of this study is to compare between Transurethral resection of the prostate and surgical treatment for prostate >75ml from where improvement of clinical symptoms and complications. Materials and methods: The study began from January 2019 to March 2020 at Tishreen University Hospital , Lattakia , Syria and was conducted on 63 cases of BPH divided into two groups, Where BPH scraping was performed on 40 patients and open surgery was performed on 23 patients. Follow up was done by measuring IPSS after surgery for each patient and detecting the presence of pre-existing complications. Results: Mean follow up was 3-7 months. The mean value of IPSS after TURP was (5.5 ± 1.2 – p value < 0.0001) whereas before TURP was (23.5 ± 5.3) and the mean value of IPSS after open surgery was (5.1 ± 1.1 – p value < 0.0001) whereas before open surgery was (25.1 ± 6.1). Conclusion: The study shows up that there is no difference between the results and complications of TURP and open surgery for prostate > 75 ml with superiority of TURP on open surgery from where bleeding degree and hospitalization period and speed of going back to work. So, we can use TURP as a good treatment choice for the treatment of BPH>75 ml.